FERICIREA CUNOAŞTERII ŞI ÎNCREDINŢAREA TEZAURULUI GNOMIC - FONARI, Conf. univ. dr., Universitatea de Stat din Moldova, Victoria (BIBLIOPOLIS, 2020)
The philosopher has always tended that one’s individual ideas capture the interest of as many as possible people, by creating schools, initiating various trends. Thus, ever since ancient times we could say that the first ones who promoted the phenomenon of globalization were the philosophers. The values operated by the philosophers are not always easy to accept. They contradict the comfort of living in our century. But this comfort does not provoke the existence of happiness. The happiness is always promised by everything: in coca-cola, being presented as one of it’s factories, by the time offered for communication by means of mobile phones, by the beer, which hides under their caps the accomplishment of one’s dreams, etc. Presently are subjected to doubt such values as friendship, understanding, sympathy, which promote indifference, egoism, arrogance. Although each theory is in compliance with its empiricism, the value which exists in different periods is reflected also in the studies of the philosophers (Aristotel, Pascal, Kant, Mill, Gadamer). The philosophers, each time perceive distinction between theory and practice. In their concepts they tend to approach the ideal of life, but this concept can be interpreted also as to disfavor of the mankind. The problem of perception intervenes particularly when some aspects are engaged for modifying the whole society. This tendency is proper to the evolution of existence of man. Yet currently there is a tendency to break-up the ideas, to use deconstruction to reach the desired essence by means of already famous names. The culture in the globalization epoch shows also many alloys in apparel, communication, even nutrition. In this sense the philosophical concepts reveal the essence of the individual in social background. The problem of harmonious existence between the man and nature, man and society, man and reality, man and sentiments, man and rationales. In various enterprises is culture: culture of behavior, general culture, communication culture. It is particularly ethical factor that is determined by the philosophers to establish that harmony to survive through personality, of not being socially, economically or politically disabled.